2007
DOI: 10.1111/j.1540-8159.2007.00840.x
|View full text |Cite
|
Sign up to set email alerts
|

Automated Left Ventricular Capture Management

Abstract: This study demonstrated that the LVCM algorithm is safe, accurate, and highly reliable. LVCM worked with different types of leads and different lead locations. LVCM was demonstrated to be clinically equivalent to the manual LV threshold test. LVCM offers automatic measurement, output adaptation, and trends of the LV threshold and should result in improved ability to maintain LV capture without sacrificing device longevity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 6 publications
1
23
1
Order By: Relevance
“…Moreover, the difference in PS-LV threshold shows a trend toward a decrease at follow-up (1.5 V on average) in all the pacing configurations (Table 6), a fact that makes automatic verification of stimulation even more attractive in selected patients who have a PS-LV difference Յ3.5 V. Although LV threshold shows little variability in the majority of patients, fluctuations Ն1.5 V were reported in 8% of patients. 19 Such an event could threaten PS in those patients without cathode programmability, who have a median PS-LV difference of approximately 1.5 V (Tables 5 and 6). Programming the LV pulse width at a greater duration lowered both the LV and the PS threshold voltage, so that no consistent benefit over a 0.5-ms programming (patients who could be paced by a 100% safety margin) was observed ( Table 6).…”
Section: Response To Crt and Ps Managementmentioning
confidence: 99%
“…Moreover, the difference in PS-LV threshold shows a trend toward a decrease at follow-up (1.5 V on average) in all the pacing configurations (Table 6), a fact that makes automatic verification of stimulation even more attractive in selected patients who have a PS-LV difference Յ3.5 V. Although LV threshold shows little variability in the majority of patients, fluctuations Ն1.5 V were reported in 8% of patients. 19 Such an event could threaten PS in those patients without cathode programmability, who have a median PS-LV difference of approximately 1.5 V (Tables 5 and 6). Programming the LV pulse width at a greater duration lowered both the LV and the PS threshold voltage, so that no consistent benefit over a 0.5-ms programming (patients who could be paced by a 100% safety margin) was observed ( Table 6).…”
Section: Response To Crt and Ps Managementmentioning
confidence: 99%
“…In our LV threshold stability analysis, we presumed the accuracy of the LVCM algorithm, but this assumption is reasonable given that previous work has demonstrated LVCM to be a highly reliable means of automatic evaluation of LV lead stimulation threshold irrespective of lead type, position (epicardial vs endocardial), or chronicity. 5 We evaluated LV thresholds only over a 2-week period rather than over the entire duration of follow-up available in the CareLink database, but prior analysis has shown that LV threshold variability is minimal even over longer follow-up of up to 21 months. 4 In our longevity increase analysis, we based our reference on current-generation battery and device parameters.…”
Section: Discussionmentioning
confidence: 99%
“…A 2-week time period was selected on the basis of previous studies demonstrating that this time period is highly correlated with long-term stability. 4,5 …”
Section: Methodsmentioning
confidence: 99%
“…1,67 As the number of patients with implantable cardiac devices continues to increase with current patient demographics, the need to reduce the follow-up burden increases.…”
Section: Introductionmentioning
confidence: 99%
“…A secondary objective was to evaluate the automated RA and RV CM features in high-power devices. The LV CM algorithm has already been validated in a previous CRT-D study 1 and therefore was not validated in the current clinical study.…”
Section: Introductionmentioning
confidence: 99%